2020
DOI: 10.1007/s00396-020-04648-x
|View full text |Cite|
|
Sign up to set email alerts
|

Probing the protein corona around charged macromolecules: interpretation of isothermal titration calorimetry by binding models and computer simulations

Abstract: Isothermal titration calorimetry (ITC) is a widely used tool to experimentally probe the heat signal of the formation of the protein corona around macromolecules or nanoparticles. If an appropriate binding model is applied to the ITC data, the heat of binding and the binding stoichiometry as well as the binding affinity per protein can be quantified and interpreted. However, the binding of the protein to the macromolecule is governed by complex microscopic interactions. In particular, due to the steric and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…where the brackets denote the concentrations of reactants and products, 40 and v 0 = l mol À1 is the standard binding volume. [41][42][43] Note that the binding fractions of the concentrations of products and reactants in eqn ( 9) and ( 10) have the dimension of volume nÀ2 . Hence, we have to divide by the volume factor v nÀ2 0 to define the dimensionless equilibrium constants K n .…”
Section: Modeling the Initial State Of The Charged Cathodementioning
confidence: 99%
“…where the brackets denote the concentrations of reactants and products, 40 and v 0 = l mol À1 is the standard binding volume. [41][42][43] Note that the binding fractions of the concentrations of products and reactants in eqn ( 9) and ( 10) have the dimension of volume nÀ2 . Hence, we have to divide by the volume factor v nÀ2 0 to define the dimensionless equilibrium constants K n .…”
Section: Modeling the Initial State Of The Charged Cathodementioning
confidence: 99%
“…Derakhshankhah et al’s simulations showed the non-cooperative binding between FG and zeolite nanoparticles via hydrogen bonds and electrostatic interactions of D-domain of FG [ 52 ]. Xu and Dzubiella calculated the binding free energies of lysozyme that was adsorbed onto the highly charged dendritic polyglycerol sulfate and derived the concept of a coverage-dependent binding affinity in the Langmuir model [ 53 ]. Sanchez-Guzman et al simulated oxyhemoglobin interacting with silica surfaces at pH 7 and pH 9 under different temperatures of 295 K, 322 K, 353 K, and 400 K, showing the dependence of the binding strength and structure on temperature and pH conditions [ 54 ].…”
Section: Conformation Binding Site and Strength Of Plasma Proteins On The Nanoparticlementioning
confidence: 99%
“…where V0 is the effective binding volume per binding site in the Langmuir picture. [59][60][61][62] The Langmuir binding volume V0 is a function of βεs and we calculate it for each adsorption energy by fitting the binding of neutral reactants to the one-component Langmuir isotherm (see the Supporting Information). For βεs = 1, V0 is well approximated by the shell volume divided by the saturation binding number, i.e., V0 = Vs/Nmax = 0.0288 nm 3 , i.e., as could be expected from the average available volume per particle if all Nmax 'sites' are occupied.…”
Section: Reaction Rate Theory Including Elec-trostatic Product Inhibi...mentioning
confidence: 99%
“…The V0 can be easily translated to the standard volume l/mol to refer to the standard energy of binding in experiments. [59][60][61] Furthermore, U is the surface (binding) energy experienced by the reactants…”
Section: Reaction Rate Theory Including Elec-trostatic Product Inhibi...mentioning
confidence: 99%